EXTRALINGUISTIC FACTORS OF THE FORMATION OF TOURISM TERMINOLOGY - Tojiboyeva Mohinur Sherali qizi (Journals Park Publishing, 2022)
This article is devoted to the formation and principle of the formation of the tourist terminology of the Uzbek language, such internal, external, linguistic factors as mastery, specialization of language units and the creation of new terms are used.
Keywords: language; society; extralinguistic